2013
DOI: 10.1158/1055-9965.epi-13-0522
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Serum Tocopherol Levels and the Risk of Non-Hodgkin Lymphoma: The Multiethnic Cohort

Abstract: Background Compromised immunity and chronic inflammation are thought to contribute to the development of non-Hodgkin lymphoma (NHL). Because tocopherols protect cells through antioxidant mechanisms, they may play a role in NHL etiology. Methods This nested case-control study within the Multiethnic Cohort examined the association of prediagnostic serum tocopherols levels measured in 271 NHL cases and 538 matched controls by high pressure liquid chromatography/photodiode-array detection with NHL risk. Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Epidemiological evidence regarding associations of γ-tocopherol with aging and the etiology of aging related diseases is limited and results are equivocal. While some studies reported inverse associations of γ-tocopherol with certain types of cancers [1820], null [2123] or positive associations have been found in others [20, 24]. Further, a nested case-control study with 39,242 Japanese subjects found that serum γ-tocopherol levels were inversely associated with ischemic stroke mortality in men but positively associated with hemorrhagic stroke mortality in women [25].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence regarding associations of γ-tocopherol with aging and the etiology of aging related diseases is limited and results are equivocal. While some studies reported inverse associations of γ-tocopherol with certain types of cancers [1820], null [2123] or positive associations have been found in others [20, 24]. Further, a nested case-control study with 39,242 Japanese subjects found that serum γ-tocopherol levels were inversely associated with ischemic stroke mortality in men but positively associated with hemorrhagic stroke mortality in women [25].…”
Section: Introductionmentioning
confidence: 99%